Investigations on the synthesis and characterization of silver-doped MoO3 thin films for photocatalytic applications - Olfa Kamoun; Anis Akkari; Badriyah Alhalaili; Ruxandra Vidu; Najoua Turki-Kamoun (Scientific Reports)
Abstract In this study, we aimed to enhance the photocatalytic performance of molybdenum oxide (MoO3) thin films by doping with silver (Ag) via a spray pyrolysis technique. The primary objective for silver incorporation was intended to introduce additional energy levels into the band structure of MoO3, improving its efficiency. Structural, optical, and photocatalytic properties were analyzed using X-ray diffraction (XRD) and optical spectroscopy. XRD results confirmed an orthorhombic phase with a (040) preferential orientation for all samples. Optimal crystallinity was observed with 2% Ag doping, yielding an 84 nm crystallite size, while higher doping levels reduced crystallite size. Band gap energy narrowed from 3.07 eV (undoped) to 2.94 eV (2% Ag-doped), indicating electronic structure changes. Impedance spectroscopy revealed superior electrical properties at 4% Ag doping, enhancing charge transport. Photocatalytic performance, assessed via dye degradation, showed significant improvement with silver doping, the degradation rate peaking at 4% Ag. These results demonstrate that silver doping optimizes structural and electronic properties of MoO3 thin films, leading to enhanced photocatalytic activity.